Kosa Kata Penting Di Peringkat Stam: Analisis Korpus Dalam Buku Teks - Zainur Rijal Abdul Razak; Rosni Samah; Muhammad Fauzi Jumingan; Mohd. Shahriman Abu Bakar (Universiti Teknologi Malaysia (UTM), 2024)
Having the knowledge on a huge number of vocabularies in foreign language learning is an important factor to be an expert in that particular language. At STAM level, Arabic language is being fully used in all students’ textbooks. Therefore, in order to cope with the learning, students should have the knowledge to understand the vocabularies used in their textbooks. However, the question is, do they have to focus on all the vocabularies found in their textbooks? This study aims to determine what are the vocabularies that frequently being used in STAM textbooks and their keywords. To achieve these objectives, the corpus of data that contains the text of three STAM textbooks was constructed and analyzed using computer software wordsmith 6.0. The Applications of word lists tool in the software was used to analyze the importance of a word by analyzing its frequency. Meanwhile, the keyword tool was used to specify keywords from the textbooks. The results showed that there is a certain vocabulary frequently used and should be the focus of students at this level. However, the keywords for a textbook are not necessarily the words that frequently used, but the vocabulary specific to the discussion topic of the book.